INTEGRASI FILSAFAT REALISME TERHADAP PENINGKATAN PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Fina Arianti; Oktaviani Adhi Suciptaningsih; Ade Eka Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to identify how the realism philosophy is applied in students' mathematics learning and skills in elementary schools, understand the concrete benefits of the realism philosophy in improving the quality of mathematics education, identify the principles of realism philosophy in learning, improving mathematics learning, and elementary school student involvement. The method used in this research is Systematic Literature Review (SLR) which is descriptive. Data collection was carried out by reviewing all articles related to the philosophy of realism in mathematics learning in elementary schools in the period 2019 - 2024. The articles used in this research were 20 accredited national journal articles obtained from Google Scholar, SINTA, which were accessed through the Google Scholar database. The results of this research show that integrating realism philosophy emphasizes understanding mathematical concepts as representations of observable reality, which are used to design more effective teaching strategies. Through this realism philosophy, students are invited to connect mathematical concepts with their daily experiences, thereby increasing relevance and understanding. Research shows that the application of learning methods based on the philosophy of realism, such as the use of teaching aids and real contexts, can increase student motivation and learning outcomes in elementary school mathematics learning.